Mencium dan Nyunggi Al-Qur'an Upaya Pengembangan Kajian Al-Qur'an Melalui Living Qur'an - Hamam Faizin (SUHUF, 2011)
Basically, the study of the Qurâ€™an does not always focus on the text (or what is in the text), exegesis or research into its science and knowledge.Â The study can be extended to the fields of anthropology and sociology of religionÂ in examing how people use the Qur'an in their daily lives. This is the so-called â€œliving Qur'anâ€ and the article seeks to introduce developments in mainstream Qurâ€™anic research into theÂ â€œliving Qur'anâ€. This is a field which has notÂ yetÂ received sufficient attention in textual studies of the Qurâ€™an. Studying the Qurâ€™an within the context ofÂ the â€œliving Qur'anâ€Â canÂ presentÂ an interesting alternativeÂ approach for contemporary times.